Nitrogen‐Doped Reduced Graphene Oxide Hydrogel Achieved via a One‐Step Hydrothermal Process. Issue 9 (18th July 2019) - Song, Man; Zhao, Jie; Meng, Yu; Riekehr, Lars; Hou, Peng‐Xiang; Grennberg, Helena; Zhang, Zhi‐Bin
Abstract: We report a one‐step method to efficiently achieve reduced graphene oxide hydrogel doped with nitrogen using ammonium formate as reducing reagent and nitrogen supplier by means of hydrothermal method. The resultant materials exhibit C/O atomic ratio as high as ∼10.9 and contains decent nitrogen doping (∼5.2 at. %). As a comparison, only solid precipitates of lower reduction efficiency and no nitrogen doping are obtained when L‐ascorbic acid is used. Electrochemical measurements show that the nitrogen‐doped reduced graphene oxide exhibits enhanced electrocatalytic ability for oxygen reduced reaction, indicating its great potential as low‐cost and precious‐metal‐free catalyst for energy storage applications. Abstract : A one‐step method to efficiently achieve reduced graphene oxide hydrogel doped with nitrogen using ammonium formate as reducing reagent and nitrogen supplier by means of hydrothermal method is reported. The resultant materials exhibit high C/O atomic ratio and contain decent nitrogen doping which leads to enhanced electrocatalytic ability for oxygen reduced reaction. The aerogel has great potential application as low‐cost and precious metal free catalyst for energy storage.